Urgensi Penyeragaman Kebijakan Cod Pada Marketplace Indonesia Demi Mewujudkan Perlindungan Hukum - Pardede, Grace Evelyn; Sujanto, Ferdinand (Pusat Kajian Hukum Perbankan Fakultas Hukum Universitas Jember, 2022)
The rapid development of technology has turned sales purchase transactions into modern mechanisms. Cash on Delivery (COD) is one of the best choice of mechanisms for people to sale and purchase. However, various problems arising from the COD mechanism are continuing to occur in Indonesia, ranging from the causes of incompatibility of goods to the lack of understanding of the COD itself in each Indonesia’s marketplace. These create new legal consequence, in this case the uncertainty of the rights and obligations of the courier that injured the courier in question. The absence of conclusive legal protection regarding the COD transactions makes the parties both physically and psychologically threatened. Therefore, it is necessary to conduct further research on the urgency of the COD policy unification in Indonesia’s marketplace in order to manifest legal protection for the parties. This research used normative juridical method. Furthermore, this research applied the conceptual and statute approach as well as comparative legal study. This study shows that there is a legal gap related to the COD mechanism in the marketplace in Indonesia. The existence of legal gap affects the absence of the unification of the COD mechanism policies in Indonesia. Thus, it can be ascertained that the legal protection of the parties involved in a marketplace is of paramount importance, particularly in the COD mechanism implementation. The said legal protection for the parties would be realized by the policy unification.